BUTTER PAPER AS A COST-EFFECTIVE DRESSING FOR SUPERFICIAL INTERMEDIATE THICKNESS BURN (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Majority of facial burns occur in children, which tends to be superficial intermediate type. Such wounds heal without scarring but needs dressing to prevent infection. Methods: The burn area is cleaned and sterilized butter paper is put over the wounds after dipping and soaking it in normal saline, under sterile conditions. Results: Patient treated with butter paper did not need frequent dressing changes, had less pain during treatment and removal, less infections meant reduced need for medications, hospital stay was reduced. All these resulted in reduced scars on healing.Conclusion: The use of butter paper is a cost effective therapeutic method of treatment of superficial burns. It’s efficacious in facial burns especially in children, more so in patients who cannot afford collagen or other expensive dressings.
Keywords: Superficial intermediate thickness burns; butter paper